2004
DOI: 10.1111/j.0736-8046.2004.21507.x
|View full text |Cite
|
Sign up to set email alerts
|

Unilesional (Segmental) Mycosis Fungoides Presenting in Childhood

Abstract: Mycosis fungoides is rare in children, and a unilesional presentation is also rare. A 13-year-old Kuwaiti boy with unilesional mycosis fungoides is described. Clinically he had a single indurated large plaque on the left shoulder with histopathologic features typical of cutaneous T-cell lymphoma. The diagnosis was further supported by the presence of a T-cell clone discovered through molecular biology studies of paraffin-embedded material. No other lesions were detected. The lesion showed a favorable response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Like APACHE, unilesional MF may present as an erythematous plaque with scaling; however, unilesional MF may have a more variable presentation with induration, dyschromia, purpura, or poikiloderma. In contrast to the acral sites favored by APACHE, unilesional MF presents most commonly on the breasts, axillae, or buttocks, though any skin site may be effected …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Like APACHE, unilesional MF may present as an erythematous plaque with scaling; however, unilesional MF may have a more variable presentation with induration, dyschromia, purpura, or poikiloderma. In contrast to the acral sites favored by APACHE, unilesional MF presents most commonly on the breasts, axillae, or buttocks, though any skin site may be effected …”
Section: Discussionmentioning
confidence: 97%
“…Patients with unilesional MF are described as having excellent outcomes with definitive treatment through superficial radiotherapy or excision …”
Section: Discussionmentioning
confidence: 99%
“…1,4,16 Unilesional MF usually develops as erythema or plaques, but its boundary is not highly clear. Unilesional MF can also occur in childhood, as Hodak et al 21 and Alsaleh et al 22 have reported.…”
Section: Commentmentioning
confidence: 93%
“…However, there have been no reports of extradermal spread, and all reported cases have shown a benign course. [18][19][20][21][22] Therefore, the cases reported by Yoo et al 23 as "unilesional mycosis fungoides mimicking Bowen's disease" and by Bazza et al 24 as "[m]ycosis fungoides masquerading as seborrheic keratosis" 24 might have been cases of lymphomatoid keratosis. Thus, the diagnosis of lymphomatoid keratosis requires careful clinicopathological examination to make a distinction from unilesional MF.…”
Section: Commentmentioning
confidence: 99%
“…Polarizable material was not seen. This histologic appearance raised the possibility of a cutaneous T‐cell lymphoma (CTCL) with granulomatous inflammation; however, unilateral involvement and presentation in childhood would be extremely rare (1). Immunocytochemistry demonstrated a normal CD4:CD8 T‐cell ratio, with mixed T‐cell lymphocytes and relatively few B cells.…”
Section: Case Reportmentioning
confidence: 99%